Effect of water immersion on the interlaminar and flexural performance of low cost liquid resin infused carbon fabric composites - Dell'Anno, Giuseppe; Lees, Rebecca (Elsevier Science B.V., Amsterdam., 2012)
This study investigates some potential benefits of using non-epoxy matrices in carbon fibre composites, targeting specific marine and wind energy applications. Water uptake during and after immersion for up to 28 days in deionised water at 40°C, and the effects of such conditioning on the interlaminar shear and flexural performance of the composites with isophthalic polyester, vinyl ester and urethane acrylate matrices were compared to those of equivalent composites impregnated with three grades of epoxy resin. Results demonstrated that, although the epoxy systems perform equally or better than the alternative resins in the dry state, they are also more sensitive to property degradation due to water ingress. The relatively lower water absorption and subsequent limited reduction in performance of vinyl ester and urethane acrylate composites is sufficiently promising to justify further study
Keywords: Carbon fibre; Thermosetting resin; Environmental degradation; Mechanical properties